Development of Flipbook-Based Arabic Teaching Materials to Enhance Istima' and Kalam Skills - Ade Arip Ardiansyah; Aditya Fitrah; Ahmad Farouq Al-Hamdi (UIN Sunan Gunung Djati Bandung, 2025)
The development of digital technology in the era of learning 5.0 requires interactive and contextual Arabic teaching materials. However, Istima' and Kalām learning in schools still face obstacles in the form of low student motivation and limited digital media. This condition shows the need for developing digital teaching materials that can facilitate enjoyable and sustainable listening and speaking exercises. This study aims to create digital Arabic teaching materials on Istima' and Kalām through flipbook media at MI Nurul Yakin. The method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The study results show that in the define stage, learning was still dominated by conventional methods; in the design stage, an interactive flipbook contained basic competencies, vocabulary, exercises, and evaluations. While in the development stage, the product was validated by experts with positive results. The dissemination stage was carried out through socialization and limited trials at MI Nurul Yakin, which showed positive responses from teachers and students regarding the appearance, accessibility, and clarity of the material. This research is expected to be an innovative step in improving istima' and kalām skills through digital-based Arabic language learning relevant to the modern era's needs. Although still limited in scale and time, the results show the potential for broader application. In the future, this teaching material can be used in teacher training and project-based learning to sustainably strengthen digital literacy in madrasas.